The Ottoman endgame : war, revolution, and the making of the modern Middle East, 1908-1923 - McMeekin, Sean (London : Allen Lane, 2015)
The Ottoman Endgame is the first, and definitive, single-volume history of the Ottoman empire's decade-long war for survival. Beginning with Italy's invasion of Ottoman Tripoli in September 1911, the opening salvo in what would soon spiral into a European conflict, the book concludes with the establishment of Turkish independence in the Treaty of Lausanne, 1923. This is the first time an author has woven the entire epic together from start to finish - and it will cause many readers to fundamentally re-evaluate their understanding of the conflict. The consequences, well into the 21st century, could not have been more momentous.
Includes index
Keywords: Turkey -- History -- Revolution, 1918-1923; Turkey -- History -- Mehmed V, 1909-1918; Empire 0ttoman -- Politique et gouvernement -- 1909-1918